2017
DOI: 10.1080/14681811.2017.1285387
|View full text |Cite
|
Sign up to set email alerts
|

Renewed commitments in a time of vigilance: sexuality education in the USA

Abstract: Over the past 20 years, the USA has seen more than its fair share of controversy with respect to education about sexuality, sex and intimate relationships. Attention has focused on content (abstinence-only vs. comprehensive instruction), delivery (by teachers, parents, health professionals or community educators) and context (within school and beyond). In recognition of this fact, Sex Education invited the development of a virtual special issue comprising a sample of its most impactful papers on these and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Considering that sexual debut usually occurs during adolescence and is increasingly taking place at earlier ages, adolescents need to increase their knowledge about sexuality; however, the literature indicates that they do not receive enough information from parents or other formal sources (Blanc Molina & Rojas Tejada, 2018 ; Helmer et al, 2015 ; Lindberg et al, 2016 ; Magnusson et al, 2019 ). In this study, the classes were hosted by professional figures linked to physical and mental health; this result is in line with the literature, which asserts that sex education administered during adolescence should be delivered by teachers, parents, health professionals, or community educators (Garcia & Fields, 2017 ; UNESCO, 2018 ). As outlined in the results, the number of hours for every project was variable; the cross-tabulations showed that this was not related to the involved professionals or the covered topics.…”
Section: Discussionsupporting
confidence: 81%
“…Considering that sexual debut usually occurs during adolescence and is increasingly taking place at earlier ages, adolescents need to increase their knowledge about sexuality; however, the literature indicates that they do not receive enough information from parents or other formal sources (Blanc Molina & Rojas Tejada, 2018 ; Helmer et al, 2015 ; Lindberg et al, 2016 ; Magnusson et al, 2019 ). In this study, the classes were hosted by professional figures linked to physical and mental health; this result is in line with the literature, which asserts that sex education administered during adolescence should be delivered by teachers, parents, health professionals, or community educators (Garcia & Fields, 2017 ; UNESCO, 2018 ). As outlined in the results, the number of hours for every project was variable; the cross-tabulations showed that this was not related to the involved professionals or the covered topics.…”
Section: Discussionsupporting
confidence: 81%
“…Sex education and media representations tend to emphasize the risks of sexuality, as well as girls’ and women’s responsibilities to protect themselves from these risks (Chmielewski et al, 2017; Garcia & Fields, 2017). Even current activist movements for women’s sexual well-being (such as #MeToo) are focused on the ways in which women’s bodies are in danger from men’s sexuality, emphasizing consent without recognizing the pursuit of women’s pleasure as distinct and important.…”
Section: Discussionmentioning
confidence: 99%
“…For example, gender ideologies about female sexual passivity and male sexual dominance are propagated in schoolbased sex education and from parents, media, and peers in raced and classed ways (Chmielewski et al, 2017;Garcia & Fields, 2017;Lamb et al, 2016). Girls receive the message that they should not feel sexual desire or that their desire is less important than boys' desire.…”
Section: Sexual Agency and Traditional Gender Rolesmentioning
confidence: 99%
“…Sexual education can be defined as any combination of learning experiences aimed at facilitating voluntary behavior conducive to sexual health. Sex education during adolescence has centered on the delivery of content (abstinence-only vs. comprehensive instruction) by teachers, parents, health professionals or community educators, and on the context (within school and beyond) of such delivery [ 12 ]. As regards content, the proponents of abstinence-only programs aim to help young adults avoid unintended pregnancies and sexually transmitted diseases (STDs), working on the assumption that while contraceptive use merely reduces the risk, abstinence will eliminate it entirely [ 13 ].…”
Section: Introductionmentioning
confidence: 99%